The role of ion size and π-interaction in stabilizing calix(4)arene crown ether metal complexes - Sittel, Thomas; Becker, Karolin; Polly, Robert; Müllich, Udo; Geist, Andreas; Panak, Petra (Chemistry - a European journal, 2025)
This study systematically investigates the influence of ion size on the structure and stability of complexes formed between the calix[4]arene crown ether 1,3-alt-25,27-bis(3,7- dimethyloctyl-1-oxy)calix[4]arenebenzocrown-6 (MAXCalix) and mono- and divalent ions from the alkali and alkaline earth metal series. NMR spectroscopy studies revealed that while MAXCalix efficiently coordinates large ions such as Cs+, it also forms complexes with smaller ions like Na+, highlighting the ligand's versatility. The size of the ion directly influences the complex structure, with two distinct structural subtypes identified via NMR and DFT calculations. In addition, π-interactions between the cation and the cation-facing benzene rings of the calix[4]arene backbone play an important role in stabilizing the complex. Larger ions like Cs+ benefit from π-interactions with both cation-facing rings, whereas smaller ions like K+ interact with only one ring, if any. These π-interactions are primarily drivers of the enhanced affinity for Cs+ and the resulting higher complex stability. Competitive NMR studies further confirmed that the complex stability increases with increasing ionic radius, and ions of similar size show comparable stability of their complexes.